THE EFFORT OF JUDGES IN FINDING THE SOLUTION OF DIVORCE CASE WITH RECONCILIATION VERDICT REFERS TO MAQASID AL-SHARIA PERSPECTIVE (Case Study at The Religious Court of Polewali Class 1 B) - Zulkifli Achmad; Supardin Supardin; Asni Asni (Pascasarjana UIN Alauddin Makassar, 2022)
The research aims to know the reasoning factors that divorcement is happened in Polewali’s Religious Court Class 1B, to know the factors which affect the action implemented by the judge in finding the solutions of divorcement case that will be ended peacefully to both sides in Religious Court Class 1B with reference to Maqasid al-Sharia. This research uses a Qualitative research by pairing with the research field. It also uses a sociological approach and normative. The result shows that firstly, the factors that cause the divorcement in Religious Courts Class 1 B among them is the lack of religious’ understanding. Secondly, the procedures and efforts implemented by the judge in finding the solutions of divorcement case that will be ended peacefully refer to the jobs and functions. Thirdly, the understanding to the husband and wife and family related to religious knowledges refer to the kindness concept in Maqasid al-Sharia.